Integrated analysis of BSA-seq and RNA-seq identified the candidate genes for seed weight in Brassica juncea - Yang, Bin; Yang, Liu; Kang, Lei; You, Liang; Chen, Hao; Xiao, Huagui; Qian, Lunwen; Rao, Yong; Liu, Zhongsong (Frontiers in Plant Science, 2024)
Introduction Brassica juncea is a major oilseed crop of Brassica. The seed weight is one of yield components in oilseed Brassica crops. Research on the genetic mechanism of seed weight is not only directly related to the yield and economic value of Brassica juncea but also can provide a theory foundation for studying other Brassica crops. Methods To map the genes for seed weight, the parental and F2 extreme bulks derived were constructed from the cross between the heavy-seeded accession 7981 and the light-seeded one Sichuan yellow (SY) of B. juncea, and used in bulk segregant sequencing (BSA-seq). Meanwhile, RNA-sequencing (RNA-seq) was performed for both parents at six seed development stages. Results Our results showed that a total of thirty five SNPs were identified in thirty two genes located on chromosomes A02 and A10, while fifty eight InDels in fifty one genes located on A01, A03, A05, A07, A09, A10, B01, B02 and B04. The 7,679 differentially expressed genes were identified in developing seeds between the parents. Furthermore, integrated analysis of BSA-seq and RNA-seq data revealed a cluster of nine genes on chromosome A10 and one gene on chromosome A05 that are putative candidate genes controlling seed weight in B. juncea. Discussion This study provides a new reference for research on Brassica seed weight and lays a solid foundation for the examination of seed in other Brassica crops.